A new frontier: building innovative partnerships to catalyze new rangelands restoration opportunities - Ferrari, Mireille; Spinelli, Madison (CGIAR System Organization, 2022)
Rangelands are having a moment. Their productive values, their environmental importance and the people who live on these lands – which we now know cover 54 per cent of the world’s land surface – are attracting the attention and focus of more researchers, academics, international organizations and even private sector. However, many of the efforts to restore the productivity and environmental services of these important landscapes continue to be dispersed and underfunded.